HASIL BELAJAR PESERTA DIDIK KELAS V SD NEGERI 9 LAHAT PADA TEMA PERISTIWA DALAM KEHIDUPAN MELALUI PENERAPAN MEDIA AUDIO VISUAL - Madian Anggraini; Toybah Toybah; Sugiono Sugiono (Universitas Sriwijaya, 2021)
ABSTRACT: This study aims to improve the fifth grade students’ learning outcomes on the theme of Events in Life in Elementary School number 9 Lahat by using audio-visual media. This research applied Classroom Action Research (CAR) with 3 cycles of action. The research subjects were the fifth grade students in class A, with a total of 9 students consisting of 4 boys and 5 girls. Data collection techniques were tests and observations. The results indicated that the scores of student learning outcomes has increased. This can be seen from the learning mastery of students in the first cycle. The average score obtained by students is 67.22 with a percentage of 55.55% which was then continued in the second cycle of 75, 22 with a percentage of 88.89%. In the third cycle, students' learning mastery increased with the acquisition of scores that reached 70 or more as many as 8 students with a percentage of 88.89%. This was supported by the results of observations on the activeness of students. In the first cycle, the score was 54.2, which was included in the moderate active category, then increased in the second cycle with a percentage of 70.37% which was included in the active category. Then, in the third cycle with the percentage is 819% and is included in the very active category. The use of audio-visual media can improve the learning outcomes of fifth grade students of Elementary School Number 9 Lahat on the theme of Events in Life. Keywords: Audio Visual Media, Learning OutcomesABSTRAK: Penelitian ini bertujuan untuk meningkatan hasil belajar peserta didik pada tema Peristiwa dalam Kehidupan di Kelas V SD Negeri 9 Lahat dengan media audio visual. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan 3 siklus tindakan. Subjek penelitian adalah peserta didik kelas V A, yang berjumlah 9 peserta didik terdiri dari 4 laki-laki dan 5 perempuan. Teknik pengumpulan data yang digunakan yaitu tes dan observasi. Hasil penelitian menunjukkan bahwa nilai hasil belajar peserta didik mengalami peningkatan, hal ini terlihat dari ketuntasan belajar peserta didik di siklus I nilai rata-rata yang diperoleh peserta didik sebesar 67,22 dengan persentase 55,55% yang kemudian dilanjutkan pada siklus II sebesar 75,22 dengan persentase 88,89%. Pada siklus III ketuntasan belajar peserta didik meningkat dengan perolehan nilai yang mencapai 70 atau lebih sebanyak 8 peserta didik dengan persentase sebesar 88,89%. Hal ini didukung dari hasil observasi, keaktifan peserta didik yang mengalami peningkatan, pada siklus I dengan persentase 54,2 dan termasuk dalam kategori cukup aktif, kemudian meningkat pada siklus II dengan persentase 70,37% yang termasuk kategori aktif, kemudian pada siklus III dengan persentase 819% dan termasuk dalam kategori sangat aktif . Melalui penggunaan media audio visual dapat meningkatkan hasil belajar peserta didik kelas V SD Negeri 9 Lahat pada tema Peristiwa dalam Kehidupan.Kata kunci: Media Audio Visual, Hasil Belajar